Elementos essenciais à implementação de equipes: um estudo de caso da indústria de papel - Bejarano, Viviane Carvalho (2006)
While commercial literature stimulates the development of teams in the workplace, empirical studies are limited, and existing texts normally focus on the internal factors influencing teams, especially on leadership. This study investigated external factors, relating them to three elements considered essential in the implementation of teams: structure, strategy and selection. The company was chosen according to the following criteria: mid-sized or large company (where it would be possible to find real teams); conducive organizational structure and the presence of strategic necessity to use teams. The company studied, a subsidiary of a multinational with more than 300 employees in the state of Paraná, Brazil, fit the criteria. The research involved all employees who participate in work-teams or their implementation. Data was collected between July 1st,, 2005 and March 21st, 2006: In the first phase, 22 employees chosen according to the company’s organizational chart, were interviewed. Sixtynine work groups were mapped, 21 of them possible teams. In the second phase, 106 participants answered 106 questionnaires about the company and 114 about their team. Questionnaires were analyzed based on point averages on the Likert scales used, from 1-5. At least 18 real teams were confirmed in the second stage, all with a high degree of maturity (average 4,08; scale 1-5) and elevated performance (average 8,5; scale 1-10), demonstrating that the company possesses mature and effective teams. These results indicate that the environment for the development of teams - including high-performance teams - does exist and is probably related to the elements adopted with relative success by the company, which are: Strategic commitment (average 3,49), using measurable actions for the development and maintenance of teams; making efforts in structure re-organization (average 3,3) and showing an adequate perception of the ideal structure; and selection, which, albeit not being directed specifically for the formation of teams, is compensated by a continuous process of rearrangement of qualified people with positive attitudes about collaborative work. There weren’t significant variations in the averages of groups of participants (top-management, middle-management; production staff), demonstrating a shared and probably realistic vision of the company.